The Quest for Identity and Individuality in Zora Neale Hurston’s Their Eyes Were Watching God - MENAGGUER, DJEBNOUN, Ouafa Mamma (University of Eloued جامعة الوادي, 2018)
تسلط هذه الأطروحة الضوء على موضوع الهوية والفردية في رواية زورا نيل هارستن "كانت أعينهم تترقب السماء" (1937) حيث تعيش بطلة هذه الرواية "جاني" رحلة طويلة لتحقيق ذاتها وهويتها في مجتمع أبوي من خلال ثلاث زيجات. ومن هنا، فأن الدراسة الحالية لها هدفان رئيسيان: أولاً، ارتأينا الإشارة إلى أهم مراحل الأدب الإفريقي الأمريكي بالإضافة إلى جذور قضية الهوية ضمن التقليد الأدبي الأفريقي الأمريكي. ثانياً، تهدف هذه الدراسة إلى تحلي لرحلة البطلة النفسية بحثاً عن هويتها وشخصيتها كما تسعى للبحث عن القوى الدافعة التي ساهمت في تحقيق استقرار جاني. لهذا، قمنا بتحليل شخصية البطلة بتطبيق منهج التحليل النفسي وقد توصلنا إلى أن نجاح جاني في تحديد هويتها وفرديتها في نهاية الرواية يعود إلى مثابرتها في تحدي العقبات المختلفة التي تعوق إعادة تشكيل هويتها الحقيقية.This dissertation attempts to investigate the theme of identity and individuality in Zora Neale Hurston’s Their Eyes Were Watching God (1937). Janie, the protagonist of the novel, undergoes a long journey of self-realization through three marriages to recognize her identity in a patriarchal society. Accordingly, the current study has two main goals. First, it points out the most significant stages of the African American literature as well as the roots of the identity issue within the African American literary tradition. Secondly, it aims at analyzing the psychological journey of the heroine in search for her identity and individuality looking for the driving forces that contribute to the achievement of Janie's stability. In doing so, this research endeavors to spotlight the novel from a psychoanalytical lens. For its framework of analysis, the study draws on psychoanalytical approach. As for the findings, the study reveals that Janie's success to define her identity and individuality at the end of her journey is due to her perseverance to overcome the various obstacles that impede reshaping her real identity.
Keywords: الأدب الإفريقي الأمريكي،الهوية،الفردية،المجتمع الأبوي، منهج التحليل النفسي; African American Literature, Identity, Individuality, Patriarchal Society, Psychoanalytical Approach.